2014
DOI: 10.14260/jemds/2014/2961
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Consideration in Patients of Down’s Syndrome

Abstract: The perimenarcheal onset of polycystic ovarian syndrome (PCOS) has long been recognized, through both its pathophysiology and the frequent onset of hirsutism and menstrual irregularities in this age group. However, there is often a delay in diagnosing PCOS in adolescence because menstrual irregularity is frequently thought to be normal in the first 2 or 3 years after menarche, particularly if clinical signs of hyperandrogenism such as hirsutism or acne are mild or absent. This was a Cross-sectional Study consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Children with Down's syndromes have usually polycythemic (>70% hematocrit) and phlebotomy may be required if hematocrit>80%, otherwise there is chances of circulatory failure 5 . There is a well-recognised association between DS and endocrine disease, particularly thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Children with Down's syndromes have usually polycythemic (>70% hematocrit) and phlebotomy may be required if hematocrit>80%, otherwise there is chances of circulatory failure 5 . There is a well-recognised association between DS and endocrine disease, particularly thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…With applications in healthcare monitoring, environmental monitoring, and various other elds, nanosensors are paving the way for advancements in personalized medicine, disease detection, and scientic research, as shown in Table 2. 1,68,[188][189][190][191]…”
Section: Overviewmentioning
confidence: 99%
“…The ongoing research and development in this arena promise to further rene sensor capabilities, paving the way for novel detection methodologies and bolstering efforts to safeguard the environment. 1,189,218,221,222 Y. Shimizu et al 223 conducted a study on the SO 2 detection capabilities of various semiconductor metal oxides, identifying WO 3 as having the highest sensitivity at 400 °C. They discovered that incorporating 1.0 wt% Ag notably enhanced this sensitivity at 450 °C.…”
Section: Application Of Nanomaterial-based Nanosensors In Healthcarementioning
confidence: 99%
“…The chronic effect of Profenofos (broad spectrum insecticide) on Swiss albino mice can be eliminated by giving the azolla filiculoides which was a suitable antioxidant. (Arun et al, 2014). The APEshows the presence of many bioactive compounds where considered a good source of high-quality protein (Kumar and Chander, 2017), It also contains almost all essential amino acids, vitamins, Beta-carotene, minerals, sapeonin and flavonoid (Muraleed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%